2022
DOI: 10.3389/fimmu.2022.995596
|View full text |Cite
|
Sign up to set email alerts
|

IgE receptor responsiveness of basophils in chronic inducible urticaria

Abstract: IntroductionChronic inducible urticaria (CIndU) is a subgroup of chronic urticaria induced by a specific stimulus. We evaluated basophil characteristics in patients with CIndU and compared with those in patients with chronic spontaneous urticaria (CSU) and healthy controls (HCs).MethodsBlood was collected from patients, and a basophil activation test (BAT) was performed. Basophil responsiveness and surface marker expression in patients with CIndU were compared with those in patients with CSU and HCs. For some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…However, Vasagar et al reported that the elevation of CD63, but not CD69 and CD203c, on the surface of basophils [ 38 ]. Mizuno et al also reported that the expression of CD63 and CD203c on the surface of basophils are elevated compared to healthy donors [ 39 ]. Expression levels of degranulation/activation markers of basophils may change during cell preparation and timing of blood collection due to the migration of activated basophils to the dermis.…”
Section: Basophil-related Molecules In Plasma and On Cell Surface Of ...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, Vasagar et al reported that the elevation of CD63, but not CD69 and CD203c, on the surface of basophils [ 38 ]. Mizuno et al also reported that the expression of CD63 and CD203c on the surface of basophils are elevated compared to healthy donors [ 39 ]. Expression levels of degranulation/activation markers of basophils may change during cell preparation and timing of blood collection due to the migration of activated basophils to the dermis.…”
Section: Basophil-related Molecules In Plasma and On Cell Surface Of ...mentioning
confidence: 99%
“…Plasma histamine level Increase [31] Spontaneous histamine release Increase [31,32] Plasma IgE level Increase [33,34] Expression level of FcεRI Increase [33,34,39] Reaction to anti-IgE antibody medication (omalizumab) Quick (few days) [34,41,42] Ratio of basophils in leukocytes Decrease [31,[33][34][35] Activation marker (CD203c, CD69 and CD63) No change or increase [33,38,39] Migration to dermis Increase [36,37] Non-or low-responder Tend to increase [31,34] Reaction to C5a and fMLP No change or increase [31,43]…”
Section: Basophil-related Conditions Changes In Csu Patientsmentioning
confidence: 99%